1991
DOI: 10.1002/mc.2940040503
|View full text |Cite
|
Sign up to set email alerts
|

Activating point mutations of the gsp oncogene in human thyroid adenomas

Abstract: The gene for the alpha polypeptide chain (alpha s) of the heterotrimeric G protein Gs can be activated to the putative oncogene gsp by specific point mutations at codons 201 and 227. Such mutations have been reported in 40% of human growth hormone-secreting pituitary adenomas and in a single autonomously functioning thyroid adenoma. We examined an archival series of 45 differentiated human thyroid tumors by polymerase chain reaction amplification and oligonucleotide hybridization to identify point mutations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0
3

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(72 citation statements)
references
References 14 publications
6
62
0
3
Order By: Relevance
“…uni-leipzig.de/winnere and Table 1 ), and between 3 and 38% for Gsa (5,19) in different reports. In particular, studies from Japan with a very high iodine supply have reported distinctly lower frequencies for TSHR mutations in hot nodules (10,20).…”
Section: Introductionmentioning
confidence: 93%
“…uni-leipzig.de/winnere and Table 1 ), and between 3 and 38% for Gsa (5,19) in different reports. In particular, studies from Japan with a very high iodine supply have reported distinctly lower frequencies for TSHR mutations in hot nodules (10,20).…”
Section: Introductionmentioning
confidence: 93%
“…A molecular basis for the TSH-independent growth and function of these tumours has been recently found: some of these tumours have somatic mutations in the alpha subunit of heterotrimeric G-protein (G s a) coupled to the TSH receptor, which stimulates the adenylyl cyclase (Lyons et al, 1990;O'Sullivan et al, 1991;Suarez et al, 1991). In other cases of thyroid hyperfunctioning adenomas activating mutations of the TSH receptor have been found in the III8 intracellular loop of the receptor (Parma et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Activating mutations may occur in exons 1-9 in these cats; however, there have been very few mutations detected in the extracellular region of the human TSHR gene (Duprez et al 1997b, Kopp et al 1997b, Parma et al 1997, Gruters et al 1998, Biebermann et al 2000. Mutations may also occur in other genes involved in the signalling transduction pathway of the TSHR, and mutations have previously been found in a Gs subunit (a protein coupled to the TSHR) gene, in both human and feline hyperthyroidism (Lyons et al 1990, O'Sullivan et al 1991, Russo et al 1995, Parma et al 1997, Murakami et al 1999, Tonacchera et al 1999, Trulzsch et al 2001, Peeters et al 2002, Vanvooren et al 2002, Georgopoulos et al 2003.…”
Section: Tablementioning
confidence: 99%